A Printed Elliptical Driver Dipole Antenna for Wireless Communications - Hyeonjin Lee; Sehansol Cheong; Rina Arum Prastyanti (LPPM Universitas Duta Bangsa Surakarta, 2022)
This work resents printed modified elliptical dipole antenna with a CPW-fed to CPS transmission. The proposed elliptical dipole antenna consiste of a CPW-fed to CPS transform, a pair of elliptical driver. The proposed antenna modified a conventional printed dipole antenna. The proposed antenna is realized a wide frequency bandwidth of 1.84GHz (4.72 – 6.56 GHz) at a return loss of less than -10 dB. The proposed antenna is able to support wireless communications applications.